Прогноз возможных трендов в развитии отечественного и мирового топливно-энергетического комплекса - Гаврилов В.П. (Общество с ограниченной ответственностью «ВНИГНИ-2», 2016)
Natural gas jets (flares) presence on the sea floor is substantiated. In particular, it was noticed in the Crimean peninsula shelf. Large jets discharge is comparable with world annual methane production, therefore their leading part in the energy balance of Russia and the world is assumed in the near future. This allows to predict considerable decrease in oil and coal extraction as it could be replaced with natural jets.
Keywords: ГАЗОВЫЕ СТРУИ; СНИЖЕНИЕ ПОТРЕБЛЕНИЯ КАМЕННОГО УГЛЯ И НЕФТИ; OIL AND COAL PRODUCTION DECREASE; GAS JETS